Water physicochemical properties shape the distribution of submerged macrophytes: implications for wetland restoration in Songnen Plain - Wang, Pei; Long, Yinian; Wang, Long; Lu, Rui; Xiao, Enrong; Wu, Zhenbin (Frontiers in Plant Science, 2025)
Submerged macrophytes play a pivotal role in maintaining the clear-water state and enhancing biodiversity in wetland ecosystems. However, the environmental mechanisms underlying their assemblage and biomass patterns remain poorly resolved in continental alkaline wetlands. Here, we conducted a 27 hydrochemical parameters analysis and dissected its relations with the distribution of submerged macrophytes in Momoge wetland of the Songnen Plain, Northeastern China. The results revealed that rock weathering and evaporation-crystallization processes jointly regulated the baseline alkalinity and salinity of the water, thereby determining 62.5% species of submerged macrophytes capable of utilizing HCO3- as an alternative carbon source. In contrast, nutrient inputs and wind-induced resuspension caused fluctuations in physicochemical conditions between light (50 < TLI ≤ 60) and moderate (60 < TLI ≤ 70) eutrophic states, resulting in Potamogeton pectinatus, Najas marina, and Chara spiralis thriving in nutrient-rich, low-transparency waters, whereas Utricularia aurea and Ceratophyllum demersum favored clearer and less nutrient-enriched conditions. These findings highlight a two-tiered environmental control over submerged macrophytes in boreal wetlands, whereby geochemical processes shape species assemblages, and nutrient dynamics and physical disturbance drive biomass allocation. We propose a restoration strategy that combines species configuration and pilot selection, prioritizing HCO3–utilizing pioneer species in degraded zones to gradually re-establish submerged macrophytes and ecosystem functions.